1985
DOI: 10.3758/bf03207158
|View full text |Cite
|
Sign up to set email alerts
|

Two techniques for investigating perception without awareness

Abstract: This note deals with the logic of recent experiments on perception without awareness. In these experiments, a stimulus is presented in such a way that some forcedchoice discrimination concerning that stimulus is at chance. Usually this involves use of a backward pattern mask. Evidence is then sought that, despite chance performance on the forced-choice discrimination (' 'lack of awareness"), processing of the stimulus is indicated in some other aspect of behavior.I shall use priming experiments as an example. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

1989
1989
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 11 publications
0
19
0
Order By: Relevance
“…Some studies have contradicted this conclusion by reporting evidence of subliminal perception with stimuli presented below performance-based thresholds (e.g., Balota, 1983;Erdley & D'Agostino, 1988;Fowler, Wolford, Slade, & Tassinary, 1981, Experiments 5 and 6;Greenwald, Klinger, & Liu, 1989;Greenwald, Klinger, & Schuh, 1995;Marcel, 1983;Niedenthal, 1990;Snodgrass, Shevrin, & Kopka, 1993), but the evidence from such studies has generally been disputed because of demonstrated or suspected methodological problems-for example, insufficient trials used for threshold determination (e.g., Dosher, 1998;Duncan, 1985;Holender, 1986;Kunimoto, 1994;Merikle, 1982Merikle, , 1992Miller, 2000;Nolan & Caramazza, 1982;Van Selst & Merikle, 1993). Thus, it is still arguable which paradigms are capable of determining whether perception occurs when stimuli are presented below the threshold for a discriminative or presence-absence response.…”
Section: Objective Definitions Based On Chance and Greater Than Chancmentioning
confidence: 90%
“…Some studies have contradicted this conclusion by reporting evidence of subliminal perception with stimuli presented below performance-based thresholds (e.g., Balota, 1983;Erdley & D'Agostino, 1988;Fowler, Wolford, Slade, & Tassinary, 1981, Experiments 5 and 6;Greenwald, Klinger, & Liu, 1989;Greenwald, Klinger, & Schuh, 1995;Marcel, 1983;Niedenthal, 1990;Snodgrass, Shevrin, & Kopka, 1993), but the evidence from such studies has generally been disputed because of demonstrated or suspected methodological problems-for example, insufficient trials used for threshold determination (e.g., Dosher, 1998;Duncan, 1985;Holender, 1986;Kunimoto, 1994;Merikle, 1982Merikle, , 1992Miller, 2000;Nolan & Caramazza, 1982;Van Selst & Merikle, 1993). Thus, it is still arguable which paradigms are capable of determining whether perception occurs when stimuli are presented below the threshold for a discriminative or presence-absence response.…”
Section: Objective Definitions Based On Chance and Greater Than Chancmentioning
confidence: 90%
“…One straightforward possibility (cf. Duncan, 1985) is to simply use a forced-choice identification task (Cheesman & Merikle, 1984). But what about other indexes?…”
Section: Which Measures Validly Index Consciousmentioning
confidence: 99%
“…For instance, the magnitude of backward masking is affected by perceptual grouping and segmentation (Caputo, 1998;Kurylo, 1997;Wolf, Chun, & Friedman-Hill, 1995) and by deployment ofselective visual attention (Enns & Di Lollo, 1997;Havig, Breitmeyer, & Brown, 1998;Michaels & Turvey, 1979;Ramachandran & Cobb, 1995;Shelley-Tremblay & Mack, 1999). Closely related, backward masking recently has been used to study visual awareness (Bachmann, 1997;Dennett, 1991;Klotz & Neumann, 1999;Klotz & Wolff, 1995;Neumann & Klotz, 1994) and its implications for the controversial field ofsubliminal perception (Duncan, 1985;Holender, 1986;Kihlstrom, 1987;Marcel, 1983). Finally, backward masking has been used to study certain clinical anomalies related to vision and brain function, such as amblyopia (Tytla & Steinbach, 1984), closed head injury (Mattson, Levin, & Breitmeyer, 1994), developmental dyslexia (Williams, LeCluyse, & Bologna, 1990;Williams, Molinet, & LeCluyse, 1989), mania (Green, Nuechterlein, & Mintz, 1994a, 1994b, and schizophrenia (Green, Nuechterlein, & Breitmeyer, 1997;Green, Nuechterlein, Breitmeyer, & Mintz, 1999;Green et aI., I994a, I994b;Merritt & Balogh, 1984;Saccuzzo & Schubert, 1981;Slaghuis & Bakker, 1995).…”
mentioning
confidence: 99%